Audit of pre hospital paediatric resuscitation - Coetzee, Abraham Jacobus (My University, 2019)
Introduction: Survival after paediatric pre-hospital cardiac arrest (CA) remains low at 4-13%. Research confirms that certain non-modifiable and modifiable factors of CA are associated with the return of spontaneous circulation (ROSC). However, no such study has been conducted in the African context. Methods: A retrospective descriptive audit was performed on all paediatric patients that received cardiopulmonary resuscitation (CPR) at a private South African Emergency Medical Services (EMS) agency (n=195) from 1 January 2011 until 1 January 2015. Non-modifiable and modifiable factors of CA were captured on an Utstein-style reporting template and the association with ROSC calculated. Results: Regarding non-modifiable factors, the majority of the cases were among males (n=122; 62.6%), aged 6-12 years (n=57; 29.2%) with the initial rhythm of asystole (n=104; 53.3%). Most of the cases were medical as opposed to trauma - related (n=130; 66.7%), of which drowning was the most common aetiology (n=62; 31.8%). Regarding modifiable factors, 21.5% of the cases were EMS witnessed. Bystander CPR prior to EMS arrival was initiated in 44.6% of the cases. The most common intervention provided by EMS was advanced airways (n=152; 77.9%), administration of adrenaline (n=151; 77.8%), intravenous access (n=113; 58.5%) and defibrillation (n=22; 11.3%). Transportation to the emergency department occurred in 45.1% of the cases, and ROSC was achieved in 42 cases (21.5%). An initial rhythm of Pulseless Electrical Activity (odds ratio=4.58; 95% CI 1.97-10.64) was the only non-modifiable factor, and bystander CPR (odds ratio=2.16; 95% CI 1.08-4.33) was the only modifiable factor significantly associated with ROSC. Conclusion: Prevention is the most effective way to avoid deaths in paediatrics. In this study, the only modifiable factor of CA was bystander CPR, highlighting that more should be done to raise the awareness and skills of citizens in the performance of basic life support.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Emergency Medicine
Keywords: Cardiopulmonary Resuscitation; Emergency medical services